Contagious Aggregation: Transmittable Protein Aggregation in Cellular Communities Initiated by Synthetic Cells - Lee, Hong-Guen; Kim, Jin Hae; Gorai, Tumpa; Ko, Young Ho; Kwon, Haw-Young; Chung, Wooseong; Hwang, Ilha; Lim, Sungsu; Kim, Yun Kyung; Shin, Kwanwoo; Chang, Young-Tae; Kim, Kimoon; et al. (American Chemical Society, 2022)
Aggregation of amyloidogenic proteins causing neurodegenerative diseases is an uncontrollable and contagious process that is often associated with lipid membranes in a highly complex physiological environment. Although several approaches using natural cells and membrane models have been reported, systematic investigations focusing on the association with the membranes are highly challenging, mostly because of the lack of proper molecular tools. Here, we report a new supramolecular approach using a synthetic cell system capable of controlling the initiation of protein aggregation and mimicking various conditions of lipid membranes, thereby enabling systematic investigations of membrane-dependent effects on protein aggregation by visualization. Extending this strategy through concurrent use of synthetic cells and natural cells, we demonstrate the potential of this approach for systematic and in-depth studies on interrogating inter- and intracellularly transmittable protein aggregation. Thus, this new approach offers opportunities for gaining insights into the pathological implications of contagious protein aggregation associated with membranes for neurotoxicity.